Natural course of acquired vitelliform lesions associated with pigment epithelial detachments in dry age related macular degeneration. Issue 6 (November 2021) - Yanık, Özge; Demirel, Sibel; Batıoğlu, Figen; Özmert, Emin
Purpose: To describe the natural history of acquired vitelliform lesions (AVLs) associated with different types of pigment epithelial detachments (PEDs) in dry age-related macular degeneration. Methods: A retrospective review of clinical examination and multimodal imaging data of patients with AVLs associated with PED(s) was performed. Results: This study included 25 eyes of 17 patients. The mean age of patients was 67.2 ± 9.7 (47–83) years. The mean follow-up time was 32.6 ± 16.2 (12–66) months, excluding four patients (five eyes) that were lost to follow-up. The mean logMAR BCVA was 0.21 ± 0.16 at baseline and 0.38 ± 0.28 at final visit ( p  = 0.016). At the end of the follow-up period, PEDs enlarged in eight eyes (40%) and were unchanged in two eyes (10%). Spontaneous resolution of the central PED(s) with AVLs was seen in four (20%) eyes. Rupture of the PED(s) occurred in four eyes (20%), with two developing central foveolar atrophy afterwards. Overall, central foveolar atrophy was seen ultimately in four eyes (20%). Conclusion: It seems that high PED size may be a risk factor for PED rupture during follow-up. 1/3 of the eyes ended up with unfavorable anatomical outcome.